2021
DOI: 10.47068/ctns.2021.v10i19.031
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of High Temperature Stress in Some Cucurbit Plants

Abstract: Some cucurbit plants (Cucumis sativus L., Cucurbita pepo L., Cucumis melo L. and Citrillus lanatus L.) were used for investigating some physiological changes and protein patterns under heat stress in plants. Leaf samples were exposed tohigh temperatures as follows 35, 40, 45, 50, 55 and 60°C. Percentage of ion leakage, chlorophyll content, leaf relative water content (RWC) and loss of turgidity, total soluble protein (TSP) content and protein profiles were determined in leaf samples kept at each temperature st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Besides, Ergin et al (2016) indicated that heat stress resulted in new protein bands and decreases/disappearance of some proteins in strawberry plants. In addition, protein bands with molecular weights ranging from 211.0 and 18.9 kDa in watermelon, 158.2 and 21.4 kDa in melon, 84.1 and 16.4 kDa in cucumber, 121.3 and 6.5 kDa in zucchini were detected, however the synthesis of these proteins was lost with increment of temperature (Ergin et al, 2021).…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 96%
See 2 more Smart Citations
“…Besides, Ergin et al (2016) indicated that heat stress resulted in new protein bands and decreases/disappearance of some proteins in strawberry plants. In addition, protein bands with molecular weights ranging from 211.0 and 18.9 kDa in watermelon, 158.2 and 21.4 kDa in melon, 84.1 and 16.4 kDa in cucumber, 121.3 and 6.5 kDa in zucchini were detected, however the synthesis of these proteins was lost with increment of temperature (Ergin et al, 2021).…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 96%
“…Tokyol and Turhan (2019) found that the TSP content of green bean genotypes reduced and/or induced with heat stress. Besides, in tomato (Turhan et al, 2021) and cucumber (Ergin et al, 2021) plants fluctuations in the TSP content under high temperatures were reported. Besides, the TSP contents of zucchini plants were not affected by the temperature, while the TSP content of melon plants did not change up to 50°C and then decreased with the increase in temperature (Ergin et al, 2021).…”
Section: Figure 3 Effects Of Heat Stress On Acidic (Panel A) and Basi...mentioning
confidence: 98%
See 1 more Smart Citation